Plasticity in stomatal density and morphology in okra and tomatoes in response to soil and water salinity - Kamululdeen, J.; Yunusa, I.; Bruhl, J.; Prychid, C.; Zerihun, Ayalsew (2016)
Okra (Abelmoschus esculentus) and tomatoes (Lycopersicum esculentum) were grown in saline (3.0 dS m-1 NaCl) and non-saline soil and irrigated with saline (2.4 dS m-1 NaCl) or non-saline water to determine the response of stomatal density and morphology to salinity. Stomata density (stomata number per unit leaf area) for tomato grown on saline soil was reduced by 33% (12 mm-2) compared with those on non-saline soils (18 mm-2); this reduction was more severe on the adaxial leaf surface where stomatal density was low. Similar reductions in stomatal density were observed in tomato irrigated with saline water. Stomata size in tomato was significantly reduced by about 20% with both types of salinity, thus the proportion of leaf surface area occupied by the stomata in salt-stressed plants, i.e., stomata area index (SAI), averaged 4.4% in salt-stressed plants compared with 5.5% in plants grown in non-saline conditions. Okra, on the other hand, maintained a similar stomatal density (average 22 mm-2) on both saline and non-saline soils, but saline irrigation marginally increased the density. In okra, the abaxial leaf surface accounted for about 68% of the total stomata under both saline and non-saline conditions. Individual stoma size in okra was increased by up to 15% on both leaf surfaces due to salinity, hence, the SAI increased from an average of 9.0% under non-saline conditions to 11.7% under saline stress. Notwithstanding the increase in SAI for okra, salinity reduced stomatal conductance by more than 50% in both crops. The stomatal conductance was generally much larger in okra than in tomato, and was as large in okra exposed to salinity as for tomato in the absence of salinity.